Computerised Terminological Databases for Translators Who Use Word Processors - Davidson, Peter (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1991)
AbstractThis paper describes the construction of a Japanese-English computer-based dictionary of financial terms for native-English speaking translators of Japanese, writing their English translation directly on to a word processor. The Japanese terms selected for entry were culled from Japanese international finance publications (books and journals) published since 1985, and are thus assured of being in current use. Two major terminological data or glossary producing software programs were tested, for "user-friendliness", minimum memory and disk space requirements. Both programs were designed for European languages, and not for ideographic Asian ones, and consequently adaptations also had to be made to mode of entry to accomodate the requirements of the Japanese language. These are discussed in the paper, as are the system of romanisation it was decided to use, and the modifications it was seen fit to make to simplify and rationalise look-up procedures.